Physiological Role of Glutamate Dehydrogenase in Cancer Cells - Moreno-Sánchez, Rafael; Marín-Hernández, Álvaro; Gallardo-Pérez, Juan C.; Pacheco-Velázquez, Silvia C.; Robledo-Cadena, Diana X.; Padilla-Flores, Joaquín Alberto; Saavedra, Emma; Rodríguez-Enríquez, Sara (Frontiers in Oncology, 2020)
NH4+ increased growth rates and final densities of several human metastatic cancer cells. To assess whether glutamate dehydrogenase (GDH) in cancer cells may catalyze the reverse reaction of NH4+ fixation, its covalent regulation and kinetic parameters were determined under near-physiological conditions. Increased total protein and phosphorylation were attained in NH4+ supplemented metastatic cells, but total cell GDH activity was unchanged. Higher Vmax values for the GDH reverse reaction vs. forward reaction in both isolated hepatoma (HepM) and liver (RLM) mitochondria favored a NH4+-fixing role. GDH sigmoidal kinetics with NH4+, ADP and leucine fitted to Hill equation showed nH values of 2-3. However, the K0.5 values for NH4+ were over 20 mM, questioning the physiological relevance of the GDH reverse reaction, since intracellular NH4+ in tumors is 1-5 mM. In contrast, data fitting to the Monod-Wyman-Changeux (MWC) model revealed lower Km values for NH4+, of 6-12 mM. In silico analysis made with MWC equation, and using physiological concentrations of substrates and modulators, predicted GDH N-fixing activity in cancer cells. Therefore, together with its thermodynamic feasibility, GDH may reach rates for its reverse, NH4+-fixing reaction that are compatible with an anabolic role for supporting growth of cancer cells.